Student Perceptions of LDKK (Latihan Dasar Kepemimpinan dan Kedisiplinan) Viewed from the Perspective of Psychological Capital at UNJANI - Endah Andriani Pratiwi; Yoga Hardianto (Green Publisher Indonesia, 2026)
This study aims to examine students' perceptions of the Basic Discipline and Leadership Training Program (Latihan Dasar Kedisiplinan dan Kepemimpinan/LDKK) from the perspective of Psychological Capital among students of Universitas Jenderal Achmad Yani (UNJANI). A quantitative explanatory research design was employed. The sample consisted of 240 undergraduate students who had participated in the LDKK program, selected through purposive sampling. Data were collected using a Psychological Capital questionnaire encompassing four dimensions self-efficacy, hope, optimism, and resilience as well as a scale measuring students' perceptions of LDKK. Data analysis was conducted using multiple linear regression with SPSS. The results indicate that Psychological Capital has a significant simultaneous effect on students' perceptions of LDKK (R² = 0.42; p < 0.001). Partially, self-efficacy, hope, optimism, and resilience each exerted a positive and significant effect on students' perceptions of LDKK (p < 0.05). These findings suggest that students with higher levels of Psychological Capital tend to perceive the LDKK program more positively. This study highlights the importance of positive psychological resources in shaping students' perceptions of leadership and discipline training in higher education. Practically, the findings suggest that integrating Psychological Capital development into the design and implementation of LDKK may enhance program effectiveness and students' overall learning experience.